Rancangan Buku Kas Digital Berbasis Web Studi Kasus: PBSS DPC Kota Batam - Yusuf Harianto Sihombing; Mohd Iqbal; Rezi Elsya Putra (Prosiding SISFOTEK, 2025)
Effective and transparent financial management is essential for the sustainability and accountability of community organizations. However, many organizations still rely on manual financial recording systems that are time-consuming and prone to errors. This study aims to develop a web-based digital cash book system to support financial management in community organizations, using BORSAK Batam City as a case study. The System Development Life Cycle (SDLC) method was applied, with data collected through interviews, observations, system testing, and questionnaires involving eight organization administrators. The system adopts a client–server architecture with a relational database and features transaction recording, real-time balance calculation, automated financial reports, data search, and audit trails. Testing results indicate a 67% increase in transaction recording efficiency and a 96% improvement in report generation time, while manual calculation errors were completely eliminated. Usability evaluation using the System Usability Scale (SUS) yielded a score of 84, classified as excellent. This study demonstrates that a web-based digital cash book system effectively enhances efficiency, accuracy, transparency, and accountability in community organization financial management.